1997
DOI: 10.1063/1.593382
|View full text |Cite
|
Sign up to set email alerts
|

Structure and superfluidity of He4 films on plated graphite

Abstract: The results of an experimental study using torsional oscillators of the superfluidity of 4He films adsorbed on hydrogen plated graphite are reported. The evolution of superfluidity with the growth of the film shows considerable structure arising from the atomic layering of the film. There is evidence that the superfluidity of a single fluid layer is strongly suppressed, possibly due to the influence of the periodic potential arising from the underlying solid layer. The behavior of two fluid layers is quite dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The oscillator operates at 1056 Hz and its motion is driven and detected capacitatively. Further experimental details and a preliminary account of some of the results are given elsewhere [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The oscillator operates at 1056 Hz and its motion is driven and detected capacitatively. Further experimental details and a preliminary account of some of the results are given elsewhere [9].…”
mentioning
confidence: 99%
“…Vertical dashed lines show layer promotions, as determined by compressibility minima obtained from vapor pressure isotherms[9].FIG. 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments rely on precise torsional oscillator techniques to measure the superfluid response. For the application of this method to the study of 4 He on graphite, see [24][25][26].…”
Section: Some Historymentioning
confidence: 99%
“…The problem of 4 He atoms deposited on solid substrates has been identified for many decades as a bosonic many-body problem that could exhibit a rich phase diagram including the possibility of dimensional crossover [1][2][3][4][5][6][7][8]. Graphite was first recognized as an ideal twodimensional substrate due to its exceptional homogeneity, [9] and extensive experimental [10,11] and theoretical studies [12][13][14] have demonstrated that under the right circumstances a superfluid He film can develop on the graphite surface. Because 4 He atoms are neutral, the many-body interactions that determine the behavior of this system are the van der Waals (VDW) interactions between He atom pairs and between He and graphite.…”
Section: Introduction a Helium On Two-dimensional Materials: A Many-b...mentioning
confidence: 99%